Transformasi Manajemen Media Massa dalam Lanskap Komunikasi Modern - Ade Anggelina Fauziah; Fitria Nur Ahmad; Afwan Syahril Manurung (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The development of information and communication technology has led to major disruption in the mass media industry. Digitalization has not only changed the way information is produced and distributed, but also influenced the organizational structure, business model, and overall media management strategy. This study aims to analyze the forms of mass media management transformation in responding to changes in the modern communication landscape. Using a qualitative approach and case study method in two mass media in Indonesia, data was obtained through literature studies and observations. The results of the study indicate that the mass media are restructuring their organizations by forming digital divisions, implementing revenue diversification strategies, and utilizing digital technology in content production and distribution. In addition, it was also found that the media faces serious challenges such as the digital competency gap, algorithmic pressure, and ethical dilemmas related to journalistic professionalism. This transformation requires media management to be adaptive, data-based, and to maintain the principles of journalistic ethics in the decision-making process. This study contributes to the development of media management theory and offers practical recommendations for industry players in facing the increasingly complex digital communication ecosystem.